2008
DOI: 10.1111/j.1399-0012.2008.00801.x
|View full text |Cite
|
Sign up to set email alerts
|

Aspergillus flavus myositis in a patient after liver transplantation

Abstract: We describe the first case of Aspergillus myositis caused by Aspergillus flavus in a liver transplant patient. The patient was a 43-year-old man who underwent liver transplantation because of end-stage hepatic cirrhosis. He experienced pain in his left calf two months after the operation. Nodules with weakness, swelling, and flaring were found in the calf two wk later. Color ultrasonic examination showed uneven resonance in the left gastrocnemius. Needle aspiration and biopsy of the muscle revealed septate hyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…Additionally, the outcome was not reported for 141 cases, whereas in 174 cases, more than 50% of the characteristics required for the analysis were lacking. Therefore, 116 individual cases in all were analyzed …”
Section: Resultsmentioning
confidence: 99%
“…Additionally, the outcome was not reported for 141 cases, whereas in 174 cases, more than 50% of the characteristics required for the analysis were lacking. Therefore, 116 individual cases in all were analyzed …”
Section: Resultsmentioning
confidence: 99%
“…Animal studies have shown that in vivo antifungal efficacy against C. bantiana is consistent with in vitro antifungal susceptibility. [22731] Despite these improved agents, failure with C. Bantiana continue to be reported. [21]…”
Section: Discussionmentioning
confidence: 99%
“…In some rare cases, muscle infection by Treponema pallidum has been reported and some patients had secondary syphilis after HIV infection [74,75]. Because fungal infection is closely related to the immune status of patients, fungal myositis is found mainly in immunocompromised patients after HIV infection or organ transplantation and Aspergillus is a common cause in these cases [76][77][78].…”
Section: Recent Findings On Infectious Myopathymentioning
confidence: 99%